Nurses’ contribuitions to care of children with intestine stomy at school (Research, Society and Development, 2021)
This study is a reflective research on the contributions of nurses to the care of children with ostomy in the school environment. Carried out in the Virtual Health Library (VHL) databases, in the following information base: International Health Science Literature (MEDLINE), Scientific Electronic Library Online (SCIELO). Children with intestinal ostomies, although they have characteristics that unite them in a special condition, are in constant development and their families need to adapt to this new lifestyle. It is noteworthy that facing this special need will lead to several changes in daily life. It is of fundamental importance to implement a service offered by a competent and qualified professional to guide ostomized children and their families about care, implementing a holistic and differentiated service. Given the above, one can reflect on the appreciation of these nurses and specialists in Stomatherapy, who are trained for such activity. It is also worth reflecting on the possibility of using these guidelines to students, because the sooner they are guided, the better their success will be in this situation.